2014
DOI: 10.4137/cmo.s19823
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protein Level in the Cerebrospinal Fluid of a Patient with Cerebral Radiation Necrosis Treated with Bevacizumab

Abstract: A 32-year-old woman underwent surgeries and radiation therapy for astrocytoma. She developed symptomatic radiation necrosis in the lesion, which caused hydrocephalus. She initially underwent ventricular drainage, because the protein level in the cerebrospinal fluid (CSF) was 787 mg/dL, which was too high for shunt surgery. Because she also had breast cancer, which was pathologically diagnosed as an invasive ductal carcinoma, standard bevacizumab therapy in combination with paclitaxel every 2 weeks was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The ability of bevacizumab to reduce CSF protein levels and facilitate VP-shunt placement was first described in an adult case with hydrocephalus caused by radionecrosis for the treatment of anaplastic astrocytoma. 12 Our study has now described bevacizumab treatment in children with low-grade gliomas with hydrocephalus and high levels of CSF proteins with the aim to reduce CSF protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of bevacizumab to reduce CSF protein levels and facilitate VP-shunt placement was first described in an adult case with hydrocephalus caused by radionecrosis for the treatment of anaplastic astrocytoma. 12 Our study has now described bevacizumab treatment in children with low-grade gliomas with hydrocephalus and high levels of CSF proteins with the aim to reduce CSF protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Recently, it has been used to improve vision in children with OPG, 11 and cases have been reported that suggest its efficacy to decrease CSF protein concentration in radiation necrosis context. 12 OPG are known to cause elevated CSF protein concentrations. 7 We report two patients with OPG and high CSF protein levels that underwent bevacizumab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study on mice showed that BEV not only inhibited angiogenesis but also enhanced the cytotoxicity of cisplatin and promoted apoptosis of tumor cells as a chemosensitizer [38]. It has also been found that low-dose BEV can also be used to treat brain edema due to radiotherapy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation necrosis is proposed to occur due to vascular damage and proliferation, therefore bevacizumab, an angiogenesis inhibitor, treats the underlying cause of symptom manifestation [12]. Bevacizumab has been shown to reduce angiogenesis in patients thereby limiting edema and proteinopathies around the radiation site [18]. Bevacizumab can limit prolonged dexamethasone therapy.…”
Section: Discussionmentioning
confidence: 99%